The Chemistry of Medical and Dental Materials - Nicholson, John W. (ISSN., 2020)
The Chemistry of Medical and Dental Materials examines the properties and interactions of these materials within the body at a molecular level, with accounts of the surgical procedures used, as well as extensive coverage of the possible biological reactions to the presence of foreign materials in the body.